Respostas

2014-06-27T00:19:49-03:00
A) x = √(6x-8)
x² = [√(6x-8)]²
x² = 6x - 8
x² - 6x + 8 = 0, p/ a = 1, b = -6 e c = 8
Δ = (-6)² - 4(1)(8) = 36 - 32 = 4
x' = [-(-6) + √4]/2.1 = (6+2)/2 = 4
x" = [-(-6) - √4]/2.1 = (6-2)/2 = 2
S={2, 4}
Verificação:
- Se x = 2
2 = √(6.2-8)
2 = √(12-8)
2 = √4
2 = 2
- Se x = 4
4 = √(6.4-8)
4 = √(24-8)
4 = √16
4 = 4
..............
b) √(3+x) = √(9-x)
[√(3+x)]² = [√(9-x)]²
3 + x = 9 - x
x+x = 9-3
2x = 6
x = 6/2
x = 3
Verificação:
Para x = 3
√(3+3) = √(9-3)
√6 = √6
1 5 1
vlw :) pelo menos vc entendou já o Eduardo nao
fauta só a verificação
:/
Pronto, fiz a verificação ou prova.